Efektivitas Dana Desa dalam Pembangunan Pertanian Pedesaan: Studi Kasus di Desa Donowarih Kecamatan Karangploso Malang - Irene Hanies Salsabella; Sutawi; Bambang Yudi Ariadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Donowarih Village is a village that has extensive agricultural land, so some of the people work in agriculture. With great potential in the agricultural sector, it will influence economic development in rural communities. The government provides funds that are managed by villages to improve village development, but the distribution of village funds for each sector is adjusted to the needs of that sector, including in the agricultural sector. This research aims to: (1) Identify the effectiveness of agricultural development, (2) Analyze the effectiveness of village fund management mechanisms (3) Identify perceptions of farmer groups in agricultural development. This research was used to obtain descriptive qualitative data. The methods used are observation, interviews, questionnaires and documentation. The focus of the research is on the mechanism for managing village funds in agricultural development. This research was carried out in Donowarih Village, Karangploso District, Malang Regency. Data analysis was carried out using validity and reliability tests on the questionnaire, then the effectiveness of the results of the questionnaire answers would be calculated using a score index. After analyzing the results of the research, the Donowarih Village Government has effectively implemented several programs to realize agricultural development, including the cultivation of goats and the Farming Road (JUT) construction program using village funds. The village fund management mechanism shows that in the planning process the answer score index is 78.75%, in the implementation process the answer score index is 81.5%, and in the accountability process the answer score index is 79% so that in each process conclusions can be drawn on village fund management has been effective. The farmer group's perception of the use of village funds in the agricultural sector for the development of facilities and infrastructure obtained an answer score index of 68.2% so that the respondent's perception was that they were effective in utilizing village funds in the agricultural sector.